Analisis Perencanaan Strategi Program Rehabilitasi Penyandang Disabilitas Sensorik di Provinsi Sumatera Selatan - Idris, Umiyati; Asteriniah, Femi; Ayusa, Nadiah Nur Rahmatullah (Program Studi Magister Ilmu Administrasi Publik STISIPOL Candradimuka, 2021)
The purpose of this study was to determine the appropriate strategic planning of the rehabilitation program for persons with sensory disabilities in South Sumatra Province. The research method used is research with a qualitative approach and the type of descriptive research. Data collection techniques used in this study were observation, interviews, and documentation. The data analysis technique used is SWOT analysis with the TOWS matrix tool. The results of this study indicate that the strategic options that can be developed in the rehabilitation program for persons with sensory disabilities in South Sumatra Province are improving the quality of entrepreneurship training, applying for business assistance to the government such as applying for assistance from Joint Business Groups (KUBE) and Productive Economic Enterprises (UEP), improving the quality of disability education, as well as increasing training or business skills. The influencing factors are government support, budget, and the role of family and community.